2018
DOI: 10.1002/dc.24087
|View full text |Cite
|
Sign up to set email alerts
|

The utility of combined mutation analysis and microRNA classification in reclassifying cancer risk of cytologically indeterminate thyroid nodules

Abstract: ObjectivesReal‐world clinical results of (1) Bethesda categorization, (2) mutation analysis, and (3) a microRNA classifier were correlated to show the utility of molecular analysis in assessing malignancy risk of indeterminate thyroid nodules.MethodsCytology and molecular results of clinically tested thyroid nodules were compared. An additional microRNA threshold was determined based on nodules with known disease status, establishing a 3‐tiered microRNA approach to clinical risk assessments. Expected rate of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(54 citation statements)
references
References 28 publications
3
51
0
Order By: Relevance
“…An MPT positive result placed patients at 13 times higher risk of malignancy compared to those with an MPT negative result, which carried a high probability (92%) of cancer-free survival over 2 years follow-up. These risk classifications are consistent with those reported by others who have shown that micro-RNA analysis can help reclassify cancer risk of nodules with weak driver mutations 16. We show that incorporation of microRNA testing of nodules with weak driver mutations into MPT significantly improved the rate of a negative MPT test result from 69% to 87% in our study cohort at 14% cancer prevalence.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…An MPT positive result placed patients at 13 times higher risk of malignancy compared to those with an MPT negative result, which carried a high probability (92%) of cancer-free survival over 2 years follow-up. These risk classifications are consistent with those reported by others who have shown that micro-RNA analysis can help reclassify cancer risk of nodules with weak driver mutations 16. We show that incorporation of microRNA testing of nodules with weak driver mutations into MPT significantly improved the rate of a negative MPT test result from 69% to 87% in our study cohort at 14% cancer prevalence.…”
supporting
confidence: 92%
“…6 While mutations strongly associated with malignancy, such as BRAF V600E, RET fusions, and TERT can assist in surgical decision making, other mutations considered weak drivers of cancer carry less certainty. 16,17 Multiple studies have described the ability of RNA-based risk classifiers to help resolve diagnostic uncertainty in indeterminate thyroid nodules. [11][12][13][14][15] Furthermore, residual risk of malignancy (5%-25%) is present in patients who lack any detectable mutational change.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Without additional testing, diagnostic lobectomy is often required for definitive diagnosis, concluding most frequently in benign disease in the form of nodular hyperplasia, follicular adenoma, or related noncancerous processes for which tissue resection may have been unnecessary. [7][8][9] However, inclusion of additional mutations and fusions that is not highly specific for malignancy may result in panels with lower positive predictive value (PPV). 6 When faced with an indeterminate cytology diagnosis, molecular testing is often used in routine clinical practice to further assess the risk of malignancy.…”
mentioning
confidence: 99%
“…8,[22][23][24][25] Other mutations and fusions can occur at a much lower frequency, making their PPV difficult to study and consequently not well understood. RAS mutations are the most common to indeterminate nodules and have been found in both benign and malignant nodules, presenting an uncertain PPV ranging from 15% to 70%.…”
mentioning
confidence: 99%